Comparative Genomics of Parastagonospora and Pyrenophora species - Syme, Robert Andrew (Curtin University, 2015)
The advancing technology and tools available for the important agricultural pathogens P. nodorum and P. avenaria pathosystems are leveraged here for intra-species comparison as well as comparisons to other related species. The comparisons have yielded insight into the evolutionary history of pathogen and host, insights into the mechanisms of genome evolution, and prediction of genes integral to fungal pathogenicity.